The role of probiotics in the treatment of adult atopic dermatitis: a meta-analysis of randomized controlled trials - Menul Ayu Umborowati; Damayanti Damayanti; Sylvia Anggraeni; Anang Endaryanto; Ingrid S. Surono; Isaak Effendy; Cita Rosita Sigit Prakoeswa (BMC, 2022)
Abstract Background Atopic dermatitis (AD) is chronic inflammatory skin disease that is relapsing and a serious condition that disrupts the quality of life of affected individuals. Probiotics are an immunomodulator that can enhance the immune control of atopic dermatitis. Methods All randomized controlled trials of probiotics for the treatment of adult AD published before December 2020 were included in this study from the PubMed databases and manual searching. Results Six randomized controlled trials (n = 241) were selected for this meta-analysis study. Probiotics were effective in treating adult patients with AD, indicated by the decrease in Scoring Atopic Dermatitis/SCORAD (Mean Difference (MD)  − 7.90, 95% CI − 7.25 to − 6.92; p < 0.00001; I 2 = 96%) and improved quality of life (MD − 7.68, 95% CI − 14.08 to − 1.29; p = 0.02; I 2 = 47%) which were statistically significant. However, skin severity, itch severity, Dermatology Life Quality Index (DLQI), IL-4, TFN-γ, and IgE showed no significant difference in this meta-analysis study (p > 0.05). Limitations The study found no available data for side effects of probiotics. Strength This meta-analysis analyzed a total of 241 AD patients of Asian and European origin. Conclusion The use of probiotics decreased SCORAD significantly in adult patients with AD. Probiotics can improve the quality of life of patients with AD. Capsule summary The use of probiotics in atopic dermatitis has been widely studied, with controversial results. This meta-analysis suggests that the use of probiotics can improve SCORAD and the quality of life of patients with atopic dermatitis.